A cross‐sectional observational study on the level of diabetes knowledge and related influencing factors among orthopaedic nurses. Issue 2 (23rd August 2022) - Shi, Wenli; Yao, Huilan; Guo, Zihe; Fan, Shunwu; Pan, Hongying; Liu, Chao
Abstract: Aim: To evaluate the level of diabetes knowledge and related influencing factors among Chinese orthopaedic nurses. Design: A cross‐sectional observational study. The STROBE checklist was followed. Methods: A convenience sampling method was adopted by using the Questionnaire Star application to publish online questionnaire. The nurses' diabetes knowledge levels were assessed, including a total of 34 items from the "Orthopaedic Nurses Diabetes Knowledge Mastery Questionnaire" and the "Orthopaedic Nurses General Information Questionnaire" between July 2020 and September 2020. Results: Altogether, 363 nurses participated in the survey. Their levels of diabetes‐related knowledge were moderate or lower (16.51 ± 2.96 out of 25 points). The knowledge level was closely related to five factors: professional title, education level, whether the hospital employed diabetes specialist nurses or treated outpatients, type of diabetes‐related training received and whether the individual was familiar with and adhered to current treatment guidelines. The knowledge level can be improved by providing additional training that accounts for these factors.